Judicial discretion in sentencing: contrasting reform in foreign jurisdictions with the South African system - Biggs, Meaka (Institute of Criminology, 2023)
President Nelson Mandela, in his opening address to Parliament, highlighted the fact that there are certain areas in the criminal justice system, which warrant considerable attention. It is the submission of this dissertation that the one such area is the unfettered discretion exhibited by judges in sentencing practice. This problem is not inherent to South Africa. It plagues the criminal justice systems of numerous other countries.